Patient and public involvement in research: Reflections and experiences of doctoral cancer nurse researchers in Europe - Boland, Vanessa (My University, 2023)
Purpose: Early career researchers lack guidance about patient and public involvement (PPI). The overall aim of the study was to explore the knowledge and experiences of using PPI in research among doctoral students who are registered nurses. Methods: This qualitative study included findings generated from reflective essays and focus groups involving ten registered cancer nurses who are undertaking doctoral research. The study has two stages of data collection. Participants initially wrote a reflective essay using a set of guiding questions to structure a response which was subsequently analysed. Two focus groups were then conducted to provide further insight into the themes identified in the reflective essays. Reflective thematic analysis was used to identify, name, and define the final themes. Results: There were ten participants from seven countries and were at various stages of their doctoral study. Analysis of data from reflective essays (n = 10) and focus groups (n = 2) identified four themes namely, (a) evolving recognition and appreciation of PPI, (b) embracing PPI and impact on doctoral studies, (c) the influence of the research environment, and (d) the need to empower doctoral students to integrate PPI in their research journey. Conclusion: Participants reported differing experiences of PPI awareness showing disparity in guidance about PPI for junior researchers across Europe. We recommend provision of early PPI training for doctoral students to support and encourage involvement of patients and the public in their research. Opportunities for sharing PPI experiences to help improve PPI culture in research environments that support doctoral students should be explored.
Annals of Oncology
EONS16 at ESMO
PUBLISHED
Paris, France
Keywords: Patient and public involvement; PPI; Qualitative research; Doctoral students; Junior researchers; Early career researchers; Thematic analysis; Cancer nursing; Cancer research; Reflections; Cancer